Advancing measurement infrastructure for cell and gene therapy product development. (December 2021) - Sarkar, Sumona; Lin-Gibson, Sheng
Abstract: Analytical methods are critical in the characterization and testing of cell and gene therapy products. Analytical method development occurs in parallel to product development and is refined as knowledge is accumulated during the development program. Validated analytical methods are generally required for product licensure, and steps should be taken to build towards analytical method validation as product development progresses towards release. Here we consider approaches for streamlining analytical method development via well-coordinated product and analytical method development efforts. We further discuss the importance of establishing a robust measurement infrastructure, including key aspects, such as measurement assurance strategies, measurement platforms with well-understood capabilities and limitations, standards to support rapid validation of a given measurement platform, as well as enabling tools and technologies to streamline and integrate various processes and data.